Analysising Land Use/ Land Cover Changes Classification Using Remote Sensing and GIS in Sikkim Himalayas - Prasansha Dahal; Prof. Wangshimenla Jamir; R. Supongtula; Prof. Lanusashi Longkumer (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Land refers to a region of the Earth’s surface that is composed of all or most of the components of the biosphere, which includes both biotic and abiotic components. Some of these includes vegetation, geothermal features, and animal life, soil, weather etc. However over the course of time land has undergone changes mainly due to anthropogenic factors. With the use of RS data, efficient evaluations and monitoring of large areas can be done concerning LU/LC conditions, which further empower planners and decision makers to impact the environment positively by making better decisions. This study focuses on classifying and mapping landuse/landcover of the state of Sikkim using Remote Sensing and Geographic Information System techniques . In this study supervised classification was performed between the period of 2003-2023. The important lulc classifications were vegetation, agriculture, barren land, water bodies and built up areas.